Targeted Bisulfite Sequencing Reveals DNA Methylation Changes in Zinc Finger Family Genes Associated With KRAS Mutated Colorectal Cancer - Pu, Weilin; Qian, Fei; Liu, Jing; Shao, Keke; Xiao, Feng; Jin, Qin; Liu, Qingmei; Jiang, Shuai; Zhang, Rui; Zhang, Jun; Guo, Shicheng; Zhang, Jianfeng; et al. (Frontiers in Cell and Developmental Biology, 2021)
Background: Colorectal cancer (CRC) is a leading cause of cancer death, and early diagnosis of CRC could significantly reduce its mortality rate. Previous studies suggest that the DNA methylation status of zinc finger genes (ZFGs) could be of potential in CRC early diagnosis. However, the comprehensive evaluation of ZFGs in CRC is still lacking. Methods: We first collected 1,426 public samples on genome-wide DNA methylation, including 1,104 cases of CRC tumors, 54 adenomas, and 268 para-tumors. Next, the most differentially methylated ZFGs were identified and validated in two replication cohorts comprising 218 CRC patients. Finally, we compared the prediction capabilities between the ZFGs and the SEPT9 in all CRC patients and the KRAS+ and KRAS- subgroup. Results: Five candidate ZFGs were selected: ESR1, ZNF132, ZNF229, ZNF542, and ZNF677. In particular, ESR1 (area under the curve (AUC) = 0.91) and ZNF132 (AUC = 0.93) showed equivalent or better diagnostic capability for CRC than SEPT9 (AUC = 0.91) in the validation dataset, suggesting that these two ZFGs might be of potential for CRC diagnosis in the future. Furthermore, we performed subgroup analysis and found a significantly higher diagnostic capability in KRAS+ (AUC ranged from 0.97 to 1) than that in KRAS- patients (AUC ranged from 0.74 to 0.86) for all these five ZFGs, suggesting that these ZFGs could be ideal diagnostic markers for KRAS mutated CRC patients. Conclusions: The methylation profiles of the candidate ZFGs could be potential biomarkers for the early diagnosis of CRC, especially for patients carrying KRAS mutations.